Cross sectorial collaboration to prevent foodborne outbreaks - Viegas, Silvia (2015)
Introduction: Foodborne outbreaks (FBO) caused by consumption of contaminated foods represent an important cause of morbidity and mortality worldwide. FBO are associated with the degree of development of national regulations on food safety, food hygiene, food handlers health, health literacy and food handling practices across all of the society. Information from epidemiological surveillance, integrating human, veterinary and environmental areas are essential to identify risk factors to support risk management and burden minimization activities directed at these preventable diseases. Prevention of FBO can be optimized by teaching good food safety practices to different target populations, including consumers, food handlers and health educators.